Simulation Modeling of Air and Droplet Temperatures in the Human Respiratory Tract for Inhaled Tobacco Products - Asgharian, Bahman; Price, Owen; Creel, Amy; Chesnutt, Jennifer; Schroeter, Jeffry; Fallica, Jonathan; Erives, Gladys; Rasheed, Nashaat; Chemerynski, Susan (Annals of biomedical engineering, 2023)
Respiratory tract dosimetry predictions for inhalation of tobacco product smoke and aerosols are sensitive to the values of the physicochemical properties of constituents that make up the puff. Physicochemical property values may change significantly with temperature, particularly in the oral cavity and upper airways of the lung, where the puff undergoes adjustments from high temperatures in the tobacco product to reach body temperature. The assumption of fixed property values may introduce uncertainties in the predicted doses in these and other airways of the lung. To obtain a bound for the uncertainties and improve dose predictions, we studied temperature evolution of the inhaled puff in the human respiratory tract during different puff inhalation events. Energy equations were developed for the transport of the puff in the respiratory tract and were solved to find air and droplet temperatures throughout the respiratory tract during two puffing scenarios: 1. direct inhalation of the puff into the lung with no pause in the oral cavity, and 2. puff withdrawal, mouth hold, and puff delivery to the lung via inhalation of dilution air. These puffing scenarios correspond to the majority of smoking scenarios. Model predictions showed that temperature effects were most significant during puff withdrawal. Otherwise, the puff reached thermal equilibrium with the body. Findings from this study will improve predictions of deposition and uptake of puff constituents, and therefore inform inhalation risk assessment from use of electronic nicotine delivery systems (ENDS) and combusted cigarettes.